2020
DOI: 10.3390/jcm9030735
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Morphine Treatment on Infarct Size and Reperfusion Injury in Acute Reperfused ST-Elevation Myocardial Infarction

Abstract: Current evidence regarding the effect of intravenous morphine administration on reperfusion injury and/or cardioprotection in patients with myocardial infarction is conflicting. The aim of this study was to evaluate the impact of morphine administration, on infarct size and reperfusion injury assessed by cardiac magnetic resonance imaging (CMR) in a large multicenter ST-elevation myocardial infarction (STEMI) population. In total, 734 STEMI patients reperfused by primary percutaneous coronary intervention <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Controversial reports on the impact of morphine and opioid agonists on mortality rate and myocardial damage post MI and PCI have been published suggesting a cardioprotective [ 158 160 ], adverse effect [ 161 163 ] or no significant change [ 164 , 165 ]. In reperfused STEMI patients, CMR analysis suggested contradictory results by different studies as no impact of morphine on microvascular obstruction (MVO) [ 165 ] versus an adverse effect exacerbating the myocardial and microvascular damage (MVO) post PCI [ 162 ]. Future clinical trials are warranted to assess the effect of opioids on coronary microvascular function in post MI and Post-PCI patients to determine the safety of using opioid analgesics for pain treatment of ischemic cardiovascular patients.…”
Section: Opioids and Coronary Microvascular Functionmentioning
confidence: 99%
“…Controversial reports on the impact of morphine and opioid agonists on mortality rate and myocardial damage post MI and PCI have been published suggesting a cardioprotective [ 158 160 ], adverse effect [ 161 163 ] or no significant change [ 164 , 165 ]. In reperfused STEMI patients, CMR analysis suggested contradictory results by different studies as no impact of morphine on microvascular obstruction (MVO) [ 165 ] versus an adverse effect exacerbating the myocardial and microvascular damage (MVO) post PCI [ 162 ]. Future clinical trials are warranted to assess the effect of opioids on coronary microvascular function in post MI and Post-PCI patients to determine the safety of using opioid analgesics for pain treatment of ischemic cardiovascular patients.…”
Section: Opioids and Coronary Microvascular Functionmentioning
confidence: 99%
“…The guidelines for the management of AMI in patients with STEMI continue to recommend intravenous morphine as a drug of choice for the alleviation of chest pain, with a class IIA indication [10]. Morphine administration is expected to reduce sympathetic tone and decrease venous return, which leads to increased cardiac workload [11] and results in smaller infarcts and signi cantly less microvascular obstruction determined by cardiac magnetic resonance [12]. Nevertheless, studies have revealed a correlation between morphine use and worse mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients were continuously controlled for shivering, it cannot be ruled out that subclinical shivering led to more stress in this group. Conversely, data from Eitel et al suggest a potential positive impact of opioids on infarct size and reperfusion injury in STEMI patients [22]. Although this effect was only seen in early presenters (≤120 min), central nervous effects of opioids may impact infarct size, and that may have diminished the effect of MTH.…”
Section: Copeptin As Ubiquitous Biomarker For Circulatory Stressmentioning
confidence: 97%